The assessment value of pathological condition of serum Adiponectin and Amylin in primary osteoporosis and its correlation analysis with bone metabolism indexes - Wang, XiaoJie; Bai, Xue; Miu, Ying; Chen, Pan; Yan, PiJun; Jiang, ChunXia (Journal of Medical Biochemistry, 2022)
Objective: To explore the assessment value of pathological condition of serum adiponectin (APN) and Amylin in primary osteoporosis (POP) and their correlation with bone metabolism indexes. Methods: From January 2019 to June 2021, selection of 79 cases of POP patients was as the research objects. Test of the bone density of the patients was conducted, and clinical grading of POP was via T value (normal, mild, moderate, severe). Analysis of the assessment value of pathological condition of serum APN and Amylin for POP and their association with bone metabolism indexes in patients was performed. Results: APN and Amylin in patients were declined with POP’s aggravation. Patients with APN of 5.15 μg/mL or less and Amylin of 15.38 pmol/L or less were risk factors influencing the aggravation of pathological condition of POP (P < 0.05); The area under the curve (AUC) of combined detection of APN and Amylin to assess the severity of POP was elevated vs. alone test of Amylin (P < 0.05); 25-hydroxyvitamin D (25-(OH) D) and total type 1 procollagen amino-terminal propeptide (t-PINP) in patients were descended with the aggravation of pathological condition of osteoporosis (P < 0.05), while no distinct differences were presented in the three groups of type I collagen hydroxyl terminal peptide β degradation product (β-CTX) and N-terminal osteocalcin (N-MID) (P > 0.05); APN, Amylin, 25-(OH)D, β-CTX and t-PINP were negatively linked with POP clinical grade (P < 0.05); APN and Amylin were associated with 25-(OH) D, β-CTX, t-PINP (P < 0.05), and APN and Amylin were not linked with N-MID (P > 0.05). Conclusions: Serum APN and Amylin are provided with evaluation value for the severity of POP, and are associated with the bone metabolism in patients.